Final answer:
To write a system of equations that will have (-3, 7) as a solution, we can use the equations y = 2x + 13 and x + y = 4.
Step-by-step explanation:
To write a system of equations with (-3, 7) as a solution, we can use two linear equations. Let's call the variables x and y.
The first equation can be: y = 2x + 13.
When we substitute -3 for x in this equation, we get 7 = 2(-3) + 13, which simplifies to 7 = -6 + 13 and further simplifies to 7 = 7.
The second equation can be: x + y = 4. Substituting -3 for x and 7 for y, we get -3 + 7 = 4, which simplifies to 4 = 4.
So, the system of equations that will have (-3, 7) as a solution is: y = 2x + 13 and x + y = 4.